Performance Analysis of the Full-Duplex Joint Radar and Communication System - Guo, Yinghong; Li, Cheng; Zhang, Chaoxian; Yao, Yao; Xia, Bin (2021 IEEE/CIC International Conference on Communications in China (ICCC), 2021)
In this paper, we look into the issue of feasibly sharing the spectrum between the radar and communication. Towards this, we investigate the full-duplex (FD) joint radar and communication multi-antenna system, where a node labeled ComRad of dual functionality is simultaneously communicating with a downlink and an uplink users and detecting the targets of interest. The achievable joint rate regions are obtained to evaluate the performance of the converged system. First, viewing the uplink channel and radar return channel as a multiple access channel, we propose an alternative successive interference cancellation scheme, based on which the achievable communication rate is obtained. Second, in case of a unified performance metric, we derive the exact closed-form of the radar estimation rate in terms of the direction, the range and the velocity, which quantifies how much information is obtained about the targets. Numerical results indicate that sharing the radar frequency bands with the communication operation in FD mode achieves larger rate regions compared to traditional schemes.